BOARD GAME SEBAGAI MEDIA PENDIDIKAN PERDAMAIAN PEMUDA DAN PEMUDI LINTAS IMAN DI KOTA AMBON - Alce Albartin Sapulette; Yamres Pakniany (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2019)
Peace activity is a social phenomenon which has been done in order to develop a good relation among interfaith society. Many methods have been conducted which aim to create a good messagein the society. The peace activity is done among the society that has experienced social conflict in their life. Ambon is one of the conflict areas that is suitable for any peace activities. Although the conflict has finished for years, the peace activity needs to be repeated more in order to strengthen the power of peace in Ambon. This research found that board games contain togetherness value and also identity value which are important to develop the idea of peace among youngsters. This research uses qualitative methods with data collection techniques through literature study, observation and interviews. Data analysis is performed using an interactive model that includes, data reduction, data presentation and drawing conclusions. The study was conducted in March 2019 in Ambon city. The purpose of this study was to determine the values of board games in building peace between youth and cross-faith young women in Ambon city.